The sedimentary petrology of carbonate nodules in the Elliot Formation, Karoo Supergroup, main Karoo Basin (South Africa) - Moodley, Adam (Department of Geological Sciences, 2016)
In South Africa, fossils found in the upper part of the Elliot Formation (Stormberg Group, Karoo Supergroup) are often associated with genetically poorly-constrained carbonate nodules. The origin of carbonate nodules i.e., pedogenic versus diagenetic, is important as pedogenic carbonate nodules can be used as palaeoclimate indicators, while diagenetic nodules carry limited palaeoclimatic information on the depositional setting. This research aims to characterize the carbonate nodules of the Elliot Formation macroscopically, petrographically and geochemically and to establish a diagnostic set of criteria to enable the differentiation between pedogenic and diagenetic nodules and/or diagenetic overprint. The research techniques employed in this study range from a) macroscopic field observations of the stratigraphic relationships of the nodules to the sedimentary features of the host rocks; b) sedimentary petrography of the textural features in the nodules; and c) X-ray diffraction for the assessment of the clay composition trapped within the nodules as compared to host rocks. Macroscopic field observations have shown that carbonate nodules found in the UEF are strongly associated with host rocks that contain pedogenic features such as root traces, burrows, colour mottling, and desiccation cracks, and thus are suggestive of ancient soils. However, the microscopic analysis of the nodules reveal no evidence for biological activities but rather a range of abiotic features such as septarian cracks, circumgranular cracks, and micronodules which are more likely have resulted from physicochemical processes that may have occurred during diagenesis. Clay minerals identified by X-ray diffraction include illite, muscovite, and montmorillonite confirm the generation of the sediments under arid to semi-arid climatic conditions.